Lights and sounds : effects of congruence and musical sophistication on auditory and visual perception - Aw, Justus Jinyue (2017)
Previous research has shown that there is a relationship between the pitch of sounds and visuo-spatial height. This involves the universal cross-modal congruence effects in the sensory modalities of vision and audition. Such effects are observed, for example, when visual stimuli presented higher in visual space seem to are reacted to more quickly when an accompanying sound is also high in pitch as compared to if the sound is low in pitch. Research has also shown that musical training improves pitch perception, and the current research was carried out to establish if there is a link between the two. A measure of musical sophistication was also used in place of time spent taking music lessons; this was done in order to capture other elements that encapsulated engagement with music beyond formal training and practice. Participants of differing levels of musical sophistication were recruited. They undertook a computer-based task where moving or non-moving visual stimuli were paired with audio stimuli that rose or fell in pitch, and were asked to make decisions on whether the visual stimuli moved and the direction of its movement. Results from repeated measures ANOVA indicate that cross-modal congruence effects predicted shorter reaction times, but not greater accuracy for all participants. Repeated measures ANCOVA showed participants higher in musical sophistication were also less affected by cross-modal congruence effects.